Metastable Pluripotent States in NOD Mouse Derived ES Cells - Hanna, Jacob (2009)
Embryonic stem (ES) cells are isolated from the inner cell mass (ICM) of blastocysts, whereas epiblast stem cells (EpiSCs) are derived from the post-implantation epiblast and display a restricted developmental potential. Here we characterize pluripotent states in the non-obese diabetic (NOD) mouse strain, which prior to this study was considered “non-permissive” for ES cell derivation. We find that NOD stem cells can be stabilized by providing constitutive expression of Klf4 or c-Myc or small molecules that can replace these factors during in vitro reprogramming. The NOD ES and iPS cells appear “metastable”, as they acquire an alternative EpiSC-like identity after removal of the exogenous factors, while their reintroduction converts the cells back to ICM-like pluripotency. Our findings suggest that stem cells from different genetic backgrounds can assume distinct states of pluripotency in vitro, the stability of which is regulated by endogenous genetic determinants and can be modified by exogenous factors.